USE OF INDIVIDUAL INSTRUMENT FOR HIGH TIBIAL ALGUS OSTEOTOMY IN VARUS GONARTHROSIS - Golovakha, Maxim; Bondarenko, Stanislav; Hart, Radek; Orljanski, Weniamin (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2025)
The work purpose was to present a new method of preoperative planning of high valgus tibial osteotomy with an individual instrument. Methods. Computed tomography (CT) of the lower extremities of a patient with stage II varus gonarthrosis was used. Bone segmentation from surrounding tissues, modeling of the lower extremities, correction of the tibia axis, and construction of individual blocks for resection were performed. The individual instrument is a block for performing osteotomy with depth indication and a hole for the upper middle screw of the T-shaped plate and two individual wedges for opening the osteotomy to the marks applied to them. The surgical intervention was performed with fluoroscopy control after knee arthroscopy. Partial removal of the medial meniscus and microfracture of the cartilage defect of the medial femoral condyle were performed simultaneously. Results. The planned correction of the tibia was accurately reproduced, which was confirmed by CT after surgery. In the postoperative period, there were no complications with wound healing, loading of the limb was started after 3 weeks, walking with a cane after 6, and without additional support after 10. X-rays were performed after 6, 12 weeks and 6, 12 months after the operation. A year later, the full range of motion and symmetrical walking were restored. The individual instrument allowed for quick and accurate placement of the plate, and wedges for opening the osteotomy helped to correctly reproduce the correction and hold it during osteosynthesis. Conclusion. The use of the proposed individual instrument for high valgus tibial osteotomy was convenient, simplified some stages of the surgical intervention, and ensured accurate planned correction of the angular deformity.